2000
DOI: 10.1007/s004020000178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-dose versus fractionated irradiation on the suppression of heterotopic bone formation - an animal model-based follow-up study in rats

Abstract: The histological and enzymatic effects of single-dose irradiation of 7 Gray (Gy) versus fractionated irradiation of 5 x 2 Gy on the suppression of heterotopic ossification were examined over a period of 60 days in adult male Wistar rats (n = 57). The standardized osteogenesis model system in rats 19, 10, 11, 16, 19] was used for this purpose. The course of developing ossifications was documented quantitatively and qualitatively by means of quantitative computed tomography/osteodensitometry and digital luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…In addition, no significant difference was observed between single-dose and fractionated administration. On the contrary, Esenwein et al (Esenwein et al, 2000) obtained a markedly better effect after fractionated irradiation, at equivalent doses, in rats following the induction of HO. Again, no conclusive inferences on the effectiveness of radiation in preventing HO after brain injury could be drawn from the published data.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, no significant difference was observed between single-dose and fractionated administration. On the contrary, Esenwein et al (Esenwein et al, 2000) obtained a markedly better effect after fractionated irradiation, at equivalent doses, in rats following the induction of HO. Again, no conclusive inferences on the effectiveness of radiation in preventing HO after brain injury could be drawn from the published data.…”
Section: Discussionmentioning
confidence: 92%
“…Our unpublished data indicated that bone marrow‐derived MSC are capable of contributing to HO formation from early to later stages (data not shown), which suggests that local populations of MSC‐like cells could be the receptive cell population in this model. Consistent with this hypothesis, radiation therapy, which would reduce or eliminate local MSC, has been successfully used to prevent HO after traumatic events [41]. Unfortunately, radiation therapy is not commonly used in FOP patients due to potentially severe side effects [42].…”
Section: Discussionmentioning
confidence: 99%
“…They include local blisters, iodine, mercury, colchicum, local bleeding, sarsaparilla, nitric acid, lactic acid, phosphoric acid, thyroid extract, thiosamine, sodium citrate parathyroid extract, low calcium diet, vitamin B1, vitamin E, disodium hydrogen phosphate, beryllium, androgens, ethylenediaminetetraacetic acid, ketogenic diet, ultrasound, antimitotic agents, oestrogens, thymectomy, radiotherapy, radium implants and surgical removal of plaques. 5,[19][20][21][22] Ethane-1-hydroxy 1, 1-diphosphate showed beneficial effects on two acute cases of this disease. 23 The role of corticosteroids is uncertain.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%